Introduction to the thermodynamics of materials - Gaskell, David R (Taylor & Francis, 2014)
Highly praised as Introduction to Metallurgical Thermodynamics, this new edition has been retitled Introduction to the Thermodynamics of Materials to better reflect the increasing application of thermodynamics to the behavior of nonmetallic materials, and the transformation of metallurgy to materials. Still clearly written as an introductory textbook for undergraduate and graduate level students of materials science